The City of Pittsburgh goes to the Cloud: A Case Study of Cloud Solution Strategic Selection and Deployment. Issue 2 (January 2015) - Mu, Enrique; Stern, Howard A
Faced with diminished resources and a need to provide enhanced employee email services, the City of Pittsburgh's Chief Information Officer (CIO) had to navigate a stubborn bureaucracy to achieve his objectives. Using an IT-business alignment strategic approach to decide on a suitable IT solution, the City was able to select and deploy a cloud-based system in an objective and uncontested way. The City employed an Analytic Hierarchy Process prioritization methodology, which used various criteria obtained from the stakeholders to develop a decision-making framework to select the most suitable cloud solution. The case allows a review of best practices in the cloud solution selection process, using theoretical lenses from the fields of IT alignment, decision-making, and stakeholder management. This case study is particularly useful for learning how strategic decisions to adopt IT are made in public organizations.